Distribution of faecal indicator bacteria in tropical waters of Peninsular Malaysia and their decay rates in tropical seawater. (December 2022) - Wong, Yi You; Lee, Choon Weng; Chai, Stanley Choon Yip; Lim, Joon Hai; Bong, Chui Wei; Sim, Edmund Ui Hang; Narayanan, Kumaran; Hii, Yii Siang; Wang, Ai-Jun
Abstract: We investigated the appropriateness of faecal indicator bacteria in tropical waters. We compared total coliform (undetectable to 7.2 × 10 5 cfu 100 mL −1 ), faecal coliform (undetectable to 6.1 × 10 5 cfu 100 mL −1 ) and enterococci (undetectable to 3.1 × 10 4 cfu 100 mL −1 ) distribution in Peninsular Malaysia. Faecal indicator bacteria was highest in freshwater, and lowest in seawater (q > 4.18, p < 0.01). We also measured the decay rates of Escherichia coli and Enterococcus faecium in microcosms. In seawater, average decay rate for E. coli was 0.084 ± 0.029 h −1, and higher than E. faecium (0.048 ± 0.024 h −1 ) ( t = 2.527, p < 0.05). Grazing accounted for 54 % of both E. coli and E. faecium decay. E. coli decayed in the <0.02 μm seawater fraction (0.023 ± 0.012 h −1 ) but E. faecium sometimes grew. Seawater warming further uncoupled the response from both E. coli and E. faecium as E. faecium grew and E. coli decayed with warming. Our results suggested that the prevalence of faecal indicator bacteria in tropical waters was not due to faecal pollution alone, and this will have serious implications towards the use of these faecal indicator bacteria. Highlights: The distribution of total coliform, faecal coliform and enterococci was similar i.e., highest in freshwater and lowest in seawater. Protistan grazing could account for about half of the decay of faecal indicator bacteria in seawater. Escherichia coli decay at a higher rate that Enterococcus faecium in tropical seawater. E. faecium was able to grow in tropical seawater.